Drager Medical Systems, Inc. : technology for life - Mulligan, Paul, (SAGE Knowledge. Cases., 2017)
DRAGER Medical Systems, Inc. is a company based in Lubeck, Germany with a long history of innovation in medical instruments. The company has a strong market presence in Europe, but only modest market penetration in the United States. The success and growth of operations at Drager Medical's U.S. headquarters, near Boston, Massachusetts, is critical to sustaining European market share and improving the company's U.S. market share. This case describes the preparations for a proposed consolidation of manufacturing operations into the existing office site currently housing related research and development, management, and marketing personnel. The prime challenges outlined in the case are twofold: modify the assembly operations to handle potential increased demand in a space with a 45% smaller footprint, and significantly improve production efficiency. Students have the opportunity to assess the proposed plans from both operational and financial performance perspectives and argue for changes, where warranted.